Assessing the Operational Impacts of Road Intersection using PTV Vissim Microscopic Simulation (Global Journal of Science Frontier Research, 2022)
The purpose of this study is to analysis the signalized intersection performance based on traffic volume and redesigning type of intersection. The observed data were collected at signalized roundabout intersection in Tashkent, Uzbekistan for 12 hours duration on weekdays. Traffic volume were analyzed and estimated at peak hours and estimated by level of service (LOS). Traffic volumes were projected for next 5, 10 years. The results of intersection performance were LOS C based on delay values in 2020. The next five years projected volume will be exceeding than maximum capacity from existing condition data. The study was proposed to reduce the congestion level and delays using PTV vissim software. This study is expected to help traffic engineers, planners and policy makers understand the assessment of the signalized intersections under mixed traffic conditions.